Arkansas - Macaulay, Ellen (New York Children's Press, 2002)
Presents the geography, history, government, and people of Arkansas
Introducing the natural state -- The land of Arkansas -- Arkansas through history -- Governing Arkansas -- The people and places of Arkansas -- Arkansas almanac -- Timeline -- Gallery of famous Arkansans
Includes bibliographical references (p. 76) and index
Hurg
5 8
Keywords: Arkansas -- Juvenile literature; Arkansas